Determinación de la calidad del agua por medio de bioindicadores (macroinvertebrados) en el río Illuchi, Cantón Latacunga, Provincia de Cotopaxi, período 2020-2021. UTC. Latacunga. 118 p. - Chicaiza Sarzosa, Diana Carolina (2021)
This present research work was carried out on the Illuchi River, Cotopaxi province, in order to assess water quality through the presence of bioindicators (macroinvertebrates) and their relationship to physical, chemical and microbiological analysis to determine the water quality index (ICA NSF), for this purpose three study points corresponding to the Salayambo Lagoon (P1), Hacienda Noelanda (P2) and Saragosín neighborhood (P3). For three consecutive months (November, December and January) sampling was carried out collecting a total of 1266 specimens grouped into 22 Families, 11 Orders and 7 Classes. It can be deduced that the most common and abundant individuals presented at the study points correspond to the Hyalellidae, Planariidae, Lumbricidae, Physidae, Leptoceridae and Hydrobiosidae families and the Families found in less abundance are Blephariceridae, Leptophlebiidae and Oligoneuriidae. Water quality indices were calculated using biological index-based methodologies such as "Biological Monitoring Working Party" (BMWP), Andean Biological Party (ABI), Ephemeroptera, Plecoptera, Trichoptera (EPT), and Shannon-Weaver for species diversity. According to the BMWP/col index it presented that the water status ranges from Doubtful (moderately contaminated waters) to Highly Critical (highly polluted waters), according to the ABI and EPT index the water quality is Regular-Mala, with an average biodiversity of macroinvertebrates at the 3 points of study according to the Shannon-Weaver index. The results obtained through the application of the 9 parameters of the ICA (NSF) compared to TULSMA, Annex I, Book VI, Table 3 of Water Quality Criterion for Agricultural Irrigation shows that the parameters of dissolved oxygen and fecal coliforms exceed the permissible maximum limits, this due to the presence of anthropic activities that are developed near the banks of the Illuchi River, which significantly affects the behavior and diversity of aquatic macroinvertebrates.